2017
DOI: 10.1038/lsa.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced second-harmonic generation from two-dimensional MoSe2 on a silicon waveguide

Abstract: Two-dimensional transition-metal dichalcogenides (TMDCs) with intrinsically broken crystal inversion symmetry and large second-order nonlinear responses have shown great promise for future nonlinear light sources. However, the sub-nanometer monolayer thickness of such materials limits the length of their nonlinear interaction with light. Here, we experimentally demonstrate the enhancement of the second-harmonic generation from monolayer MoSe2 by its integration onto a 220-nm-thick silicon waveguide. Such on-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 40 publications
3
134
0
Order By: Relevance
“…SHG of the bulk MoS 2 is very weak and χ (2) is around 10 −14 m/V; however, three groups simultaneously reported that SHG of monolayer MoS 2 , WS 2 , and WSe 2 increased dramatically . Later, numerous SHG studies were conducted on MoS 2 , WS 2 , WSe 2 , MoSe 2 , and MoTe 2 , and χ (2) was reported on the order of magnitude of 1 nm/V, which is much higher than the most used commercial nonlinear crystals (eg, χ (2) of BBO, KTP, and LiNbO 3 are on the order of magnitude of pm/V). The large nonlinear susceptibility of monolayer compared with bulk is ascribed to the inversion symmetry breaking.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHG of the bulk MoS 2 is very weak and χ (2) is around 10 −14 m/V; however, three groups simultaneously reported that SHG of monolayer MoS 2 , WS 2 , and WSe 2 increased dramatically . Later, numerous SHG studies were conducted on MoS 2 , WS 2 , WSe 2 , MoSe 2 , and MoTe 2 , and χ (2) was reported on the order of magnitude of 1 nm/V, which is much higher than the most used commercial nonlinear crystals (eg, χ (2) of BBO, KTP, and LiNbO 3 are on the order of magnitude of pm/V). The large nonlinear susceptibility of monolayer compared with bulk is ascribed to the inversion symmetry breaking.…”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…Chen et al demonstrated a silicon waveguide‐enhanced SHG of monolayer MoSe 2 . The working principle is displayed in Figure A (upper panel).…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
“…However, the nonlinear conversion efficiencies in monolayer TMDCs are still limited by their atomic thickness (<1 nm). Recently, much effort has been directed to enhance second‐harmonic (SH) emission intensity from TMDCs by utilizing optical microcavities and waveguides, but only relatively small enhancement factors (EFs) have been achieved in most of these works (≈5–10), resulting from the weak enhancement of the resonant field. A large EF has been reported from monolayer molybdenum disulfide (MoS 2 ) in a double‐resonant optomechanical cavity, but the complicated 3D cavity structure is not suitable for applications in on‐chip nonlinear optics.…”
Section: Introductionmentioning
confidence: 99%
“…Defect engineering has been demonstrated to be an important technique to modulate the properties of semiconductors for various applications . Particularly, defect engineering in 2D materials is critical and promising for the development of novel optoelectronic devices . Recently, single‐photon emitters have been reported from the defect states in atomically thin TMDs and h‐BN .…”
Section: Introductionmentioning
confidence: 99%